Madagascar - A Decade of Reform and Innovation in Higher Education Institutional Capacity-Building in a Developmental Perspective - Viens, Daniel; Lynch, James (World Bank, Washington, DC, 2012)
Higher education in Madagascar was in crisis in the early 1990s. Campuses were taken over by squatters and vandals. Little if any teaching was taking place because senior members of universities could not enter buildings. The quality of education was extremely low, with little or no research conducted, the staff demoralized, and the students alienated. Enrollment rose above 44,000 due to "eternal students" who were paid a grant for as long as they stayed in university. Students repeated course years as many as five times. The internal efficiency of institutions was approximately 30 percent, and external efficiency was less than 10 percent in many faculties and departments. Curricula and teaching methods were outdated and there was no system for evaluating of the institutions' performance. A large portion of the public financing was being wasted. Yet higher education was recognized by the government and the World Bank as being indispensable for generating the human resources needed for economic development and poverty alleviation. This article traces the development of a strategic partnership in higher education between the Government of Madagascar, the World Bank and other donors over a period of almost ten years.